Regulasi penyiaran : dari otoriter ke liberal - Masduki; Indonesia (Yogyakarta : LKiS Yogyakarta, 2007)
Regulation on radio broadcasting system reflected in broadcasting law in Indonesia.
Includes the text of: Undang-Undang Tentang Penyiaran.
Includes bibliographical references (p. 277-285) and index.
Keywords: Radio -- Law and legislation -- Indonesia